METODA PENETAPAN PEMENANG LELANG PENGADAAN BARANG/JASA PEMERINTAH MELALUI PENDEKATAN ANALYTICAL HIERARCHY PROCESS: Studi pada Dinas Kesehatan Kabupaten Kepulauan Mentawai - , RINAL FENDI; , Dr. Akhmad Makhfatih, M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The process of determining the winner of an auction of government procurement is part of a multi-criteria decision making must be supported by objective considerations outlined in the Indonesian Presidential Regulation No. 70 of 2012. Method evaluation conducted by knockout in the Health Office Mentawai Islands Regency, to find the winning bidder was chosen, not able to carry out the employment agreement/contract that has been agreed. This study aims to determine the winner of the auction procurement of government goods/services through the approach of Analytical Hierarchy Process (AHP) with the expert choice software version 11. The assessment was conducted at the bid evaluation stage includes assessment criteria bidders administrative, technical, price and qualifications with the value system (merit point system). The results showed the first priority is the evaluation criteria at the level of administration (54.6 percent), price evaluation (18.6 percent), the evaluation of qualifications (14.8 per cent) and technical evaluation (12 percent) with a value of 0.00059 inconsistency, from the results of expert assessment through questionnaires given sourced from bidders bid documents, then the decision alternative is CV Wina Datuk Surya as the first winner construction activities Bosua health centers at Health Office Mentawai Islands Regency. AHP is able to provide an objective and comprehensive assessment of a variety of criteria and alternatives are many options that can improve the performance of the procurement committee to assess the offer document in determining the winner of the auction procurement of goods/services that are effective and efficient. Key words: Procurement of goods/services, Criteria, AHP, Expert choice